2020
DOI: 10.1097/qad.0000000000002583
|View full text |Cite
|
Sign up to set email alerts
|

Determining standardized causes of death of infants, children, and adolescents living with HIV in Asia

Abstract: Objective: To implement a standardized cause of death reporting and review process to systematically disaggregate causes of HIV-related deaths in a cohort of Asian children and adolescents. Design: Death-related data were retrospectively and prospectively assessed in a longitudinal regional cohort study. Methods: Children under routine HIV care at sites in Cambodia, India, Indonesia, Malaysia, Thailand, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Malnutrition was the leading underlying cause of death among HIV-uninfected decedents but was more frequent in the causal chain of HIV-infected decedents as HIV disease with wasting syndrome or as morbid conditions. This finding is in line with recent studies from Asia and Uganda that reported increased mortality among HIV-infected children who have severe acute malnutrition [52,53]. The increased risk of death could be because of the synergistic immunosuppressive effects of both diseases rendering the child vulnerable to fatal infections.…”
Section: Discussionsupporting
confidence: 91%
“…Malnutrition was the leading underlying cause of death among HIV-uninfected decedents but was more frequent in the causal chain of HIV-infected decedents as HIV disease with wasting syndrome or as morbid conditions. This finding is in line with recent studies from Asia and Uganda that reported increased mortality among HIV-infected children who have severe acute malnutrition [52,53]. The increased risk of death could be because of the synergistic immunosuppressive effects of both diseases rendering the child vulnerable to fatal infections.…”
Section: Discussionsupporting
confidence: 91%
“…However, the burden observed in this current study remains high and could be explained by either undocumented previous therapeutic failure or vertical transmission of resistant viruses [36]. Regarding the immunological profile, CD4 nadir was found to be a predictor of ADRMs, with nearly three‐quarters of ALHIV with a CD4 nadir < 350 cells/μl archiving mutations in HIV‐1 reservoirs [37], highlighting the fact that close monitoring of CD4 is necessary in this vulnerable population in order to prevent the emergence of opportunistic infections [38]. Furthermore, the most prevalent ADRMs were selected by NNRTIs.…”
Section: Discussionmentioning
confidence: 99%
“…Acquired immunodeficiency syndrome (AIDS) is an important public health concern worldwide, and deprives hundreds of thousands of people of their lives each year. AIDS is the fourth major cause of human death and the leading cause of death due to infectious disease [ 1 ]. Serious opportunistic infections (OIs) are the prominent cause of death in patients with advanced AIDS, with many such infections posing a serious threat to the health of human immunodeficiency virus (HIV)/AIDS patients [ 2 ].…”
Section: Introductionmentioning
confidence: 99%